(Studi Kasus Berita Covid-19 Edisi Maret – Desember 2022) - Luk Mini Mini; Heny Triyaningsih (STISIP Widyapuri Mandiri Sukabumi, 2023)
The analysis of the journalistic code of ethics is an effort to observe something in depth about the standard norms that must be used as a reference for juornalists in acting, acting, and behaving when carrying out their profession as journalist in writing news. In this study, the researcher discusses whether the print media Radar Madura Pamekasan applies the journalistic code of ethics contained in Law No. 40 of 1999 in writing the March – December 2020 Edition of Covid-19 news and how to apply the journalistic code of ethics in writing Covid-19 news in the headlines of the daily newspaper Radar Madura Pamekasan. The result of this research is that Jawa Pos Radar Madura, Pamekasan bureau, applies the journalistic code of ethics contained in Law No. 40 of 1999 Article I states that Indonesian Journalists have the right to refuse to protect sources who do not want to know their identity or whereabouts, respect the provisions of the embarg, backround information, and off the record in accordance with the agreement. Various processes are carried out by the Jawa Pos Radar Madura print media so that the news can be published. The code of ethics is one of the main guidelines for Jawa Pos Radar Madura journalists, so that in writing the Covid-19 news, if you include your name or address, it will confirm the source or doctor in collecting data during coverage. If you include the address of the sub district village it is still common, so there are no problems in writing the news.